Safety Textbooks that Implement a Personality-Oriented Approach - Dykan, Serhii; Dehtiarova, Klavdiia; Shcherbinin, Leonid; Redkin, Ðžlexandr (International Journal of Engineering and Technology, 2018)
The present article considers a conceptual approach to the creation of a coursebook that wouldÂ implement the so-called ternary matrix, which will allow a student to effectively gain and build up knowledge. The authors illustrate how such ternary matrix can realize three-coordinate model of modern education, which consists of three interconnected processes: the subject knowledge transfer, socialization of the student and his/her cultural education. By means of the coursebook traditional descriptive text transformation into a performative text and textbook division into four blocks authors create the cognitive environment in which there is a synergistic strengthening of three interrelated information flows â€“ learning, socialization and cultural education. As a result a student-centered approach to learning and increased efficiency of learning is achieved.Â Â